Sensory Profiling of Brewed Cascara Robusta, Clove, and Using the Rate-All-That-Apply Method: Profil Sensori Seduhan Cascara Robusta, Cengkeh, dan Penggunaan Metode Rate-All-That-Apply - Firza Farianshah Difandra; Riski Ayu Anggreini; Hadi Munarko (The University of Lampung, 2026)
Cascara is a residual product of coffee cherry processing, has the potential to be utilized as a brewed beverage with a distinctive taste and aroma; however, its sensory characteristics are sometimes less favored by panelists. To enhance its sensory quality and mask undesirable flavors, the addition of cloves and cinnamon was employed. This study aimed to describe and determine the sensory attributes of cascara beverages with the addition of cloves and cinnamon using the Rate-All-That-Apply (RATA) method. Prior to the RATA assessment, total phenol content and color analyses were conducted across various concentration levels. The RATA test involved 70 panelists who evaluated 14 sensory attributes. Principal Component Analysis (PCA) results indicated that sample P1 (100% Cascara) was associated with a bitter aroma; sample P2 (90% Cascara:5% Cinnamon:5% Clove) was characterized by a bitter taste and aftertaste, sweet aroma, watery mouthfeel, and lingering sensation; sample P3 (80% Cascara: 10% Cinnamon: 10% Clove) exhibited a spicy taste, aroma, and aftertaste, along with a distinctive spice aroma; whereas samples P4 (70% Cascara: 15% Cinnamon: 15% Clove) and P5 (60% Cascara: 20% Cinnamon: 20% Clove) were associated with a yellowish color and high brightness levels. These findings suggest that the incorporation of additional ingredients may further enhance consumer acceptance and overall sensory appeal.